The Limits of American Efficiency: The Case Study of a Hurricane - Csillag, András (FOCUS: Papers in English Literary and Cultural Studies, 2024)
On Monday, 29 August 2005, the Gulf Coast of Louisiana, Mississippi and Alabama was hit by a storm causing flooding and devastation of enormous magnitude. With some 1,800 victims killed and leaving the city of New Orleans in chaos, Hurricane Katrina was the most destructive American natural disaster in living memory, comparing only to a similar one striking Galveston, Texas (1900), and the earthquake of San Francisco (1906). No major city in the US had been forced to evacuate since Richmond and Atlanta during the Civil War. About 80% of New Orleans came under water, but Katrina also flattened or flooded a number of smaller towns along the coast, for example Gulfport, Biloxi or Mobile. As New Orleans lies mostly below sea level between the banks of the Mississippi and the massive Lake Pontchartrain, disaster was only a question of time and chance. The storm caused breaches in the city’s floodprotection levees knocking out electric, water, sewage, transportation and communication systems. The historic French Quarter, the most famous part of New Orleans, was spared by the flood which, however, made hundreds of thousands of residents homeless and the city uninhabitable as a whole.